SUCCESSES OF TRANSLATED WORKS STAGED AT THE KARAKALPAK STATE THEATER OF YOUNG AUDIENCES - Nag‘metov Nokisbay Asembaevich (Web of Journals Publishing, 2025)
Karakalpak State Theater of Young Spectators is one of the most productive theaters in recent years. This article talks about the translated works staged by the theater in recent years and the successes achieved.
Keywords: Young audience theater, director, actor, performance, dramaturgy.